Stock Market Manipulation on the Hong Kong Stock Exchange - Dionigi Gerace; Charles Chew; Christopher Whittaker; Paul Mazzola (Australasian Accounting, Business and Finance Journal, 2014)
This study is the first to empirically examine stock market manipulation on the Hong Kong Stock Exchange. The dataset contains 40 cases of market manipulation from 1996 to 2009 that were successfully prosecuted by the Hong Kong Securities & Futures Commission. Manipulation is found to negatively impact market efficiency measures such as the bid-ask spread and volatility. Markets appear incapable of efficiently responding to the presence of manipulators and are characterised by information asymmetry. Manipulators were successfully able to raise prices and exit the market. This finding contradicts views that trade-based manipulation is entirely unprofitable and self-deterring. The victimisation of information-seeking investors and the market as a whole provides a strong rationale for all jurisdictions, including Australia, to have effective laws that prohibit manipulation and for robust enforcement of those laws to further deter market manipulation.
Keywords: market manipulation; market misconduct; Hong Kong Stock Exchange; market microstructure; securities regulation